Analisis dan Simulasi Parameter Model Susceptible Vaccinated Infected Recovered (SVIR) pada Penyebaran Tuberkulosis di Indonesia - Arifin Aji Nugroho; Muhammad Azhar Aziz; Ahmad Yasser Aulia Tanjung (Jurnal Integrasi Sains dan Quran, 2023)
Infectious diseases still threaten world wide. One of the most infectious is TB that is infected through Mycobacterium tuberculosis. TB Prevention is carried out by BCG vaccination, while TB treatment is carried out through DOTS. The pattern of TB transmission can be identified using the SVIR model. The TB program in Indonesia is carried out to achieve TB Elimination in 2035 and Indonesia TB-free in 2050 by taking into account three indicators, namely prevalence, incidence, and mortality. This study aims to reproduce the SVIR model, analyze the model solution and interpret the results for TB programs in Indonesia. Furthermore, the transmission pattern and predictions of three TB indicators in Indonesia are determined. Moreover, parameter simulation of contact rate is applied based on Hadis Rasululloh Saw to prevent the interaction between the infectious and noninfectious individu. The SVIR model is applied in Indonesia by estimating parameters based on data for 2004-2018. The accuracy of the model is measured based on absolute relative error in 2019 and 2020. RK Order 4 Method showed the error values of less than 5%, so that the model is quite accurate in determining TB transmission and three indicators above. The projection of the three indicators and the simulation of the contact rate showed a significant decrease. However, the TB Elimination and Indonesia TB-free has not been achieved.